Candidate Chinese Herbal Medicine Alleviates Methamphetamine Addiction via Regulating Dopaminergic and Serotonergic Pathways - Ru, Qin; Xiong, Qi; Tian, Xiang; Xu, Congyue; Li, Can; Chen, Lin; Wu, Yuxiang (Frontiers in Molecular Neuroscience, 2022)
Methamphetamine (METH) addiction and its induced mental disorders have become a severe worldwide problem. A candidate Chinese herbal medicine (CCHM) in our lab had therapeutic effects on METH-induced locomotor sensitization, however, its chemical and pharmacological profiles remain to be elucidated. The current study aimed to investigate the effect of CCHM on conditioned place preference (CPP) induced by METH and screen the main active ingredients and key targets by using network pharmacology and molecular docking methods. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment, Gene ontology (GO) analysis and protein-protein interaction (PPI) network were performed to discover the potential mechanisms. Results showed that CCHM could significantly inhibit METH-induced CPP behaviors in mice. A total of 129 components and 43 targets were screened. According to the network pharmacology analysis, ten hub targets including DRD2 and HTR3A were screened. GO analysis and KEGG enrichment showed that mechanisms of CCHM treatment of METH addiction were related to multiple pathways such as dopaminergic synapse, serotoninergic synapse, and dopamine receptor activity. Western blot results showed that the protein expression of DRD2 in nucleus accumbens and prefrontal cortex was significantly decreased in METH group, while the protein expression of HTR3A was significantly increased. These changes caused by METH could be prevented by CCHM pretreatment. The results of molecular docking showed that the five active ingredients such as (S)-Scoulerine, Hyndarin, and Beta-Sitosterol had good affinities with DRD2 and HTR3A. In conclusion, this study constructed the CCHM’s pharmacologic network for treating METH addiction based on the method of network analysis, and analyzed its major active ingredients and potential targets, indicating a new direction for further revealing its mechanisms of effect on METH addiction.